Numerical studies on plasma parameter modulation of atmospheric pressure dielectric barrier discharge via 200 kHz/13.56 MHz dual-frequency excitation - Nie, Q. Y. (2019)
The performance of atmospheric pressure dielectric barrier discharge (DBD) driven by dual-frequency sources of 200 kHz/13.56 MHz has been investigated numerically here in a one-dimensional fluid model. By varying the ratio of dual frequency excitation amplitudes, strong nonlinear coupling in the discharge is observed, with the electron density rising significantly due to the synergistic effect governing the ionization process. Moreover, it is shown that the phase shift between the dual frequencies also has an influence on the electron temperature and density. As to different high frequency components, the modulation of the electron temperature and density induced by the phase-shift also varies significantly. Those results then demonstrated the possibility of applying amplitude and/or phase modulations in a wide operation window to optimize the plasma parameters in dual-frequency DBDs with fixed frequencies.